The CRO Laudato Si’ Project: Goals, Activities, and Social Outcomes - Brgles, Miriam Mary; Turza, Zoran; Žagmešter, Marija (Studia Ecologiae et Bioethicae, 2022)
On the eve of 2020, and the fifth anniversary of the publication of the Encyclical Letter - Laudato Si’. On the care for the common home at the Catholic University of Croatia, the scientific-professional project CRO Laudato Si’ was launched. The project team was composed of scientists from different disciplines, and the project partners were the National Fraternity of the Franciscan Secular Order and the Franciscan Youth. As part of the project, scientific and practical activities were carried out. One of the main scientific activities was empirical scientific research, which was conducted, using a survey method over several months in 2020. The paper will present the results of the research, related to the role of the project in the knowledge of the encyclical Laudato Si’ and the awakening of interest in the encyclical, according to the socio-demographic characteristics of the respondents. The results show that men have heard of the encyclical Laudato Si’ to a somewhat greater extent than women. The largest number of respondents, who heard about the encyclical for the first time through the project, are those who belong to the youngest age group, followed by those with high school education. Arousing interest in Encyclical Letter topics is more encouraged among women, those over 65 years old, respondents with completed primary school, and those who are self-employed or retired.